2003
DOI: 10.1097/01.brs.0000065482.41115.b4
|View full text |Cite
|
Sign up to set email alerts
|

Metal Concentrations in the Serum and Hair of Patients With Titanium Alloy Spinal Implants

Abstract: Approximately one third of patients with titanium alloy spinal implants exhibited abnormal serum or hair metal concentrations at a mean time of mean 5.1 years after surgery. Titanium or aluminum may travel to distant organs after dissolution of metals from the spinal implants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
68
2
5

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(75 citation statements)
references
References 25 publications
0
68
2
5
Order By: Relevance
“…Leopold et al reported a failed patellar component in total knee arthroplasty, with elevated serum titanium at least 20 times higher than normal values [16,21]. The highest titanium serum concentrations of our series were found in cases of mechanical complications such as stem fixation (subsidences) or neck impingement.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Leopold et al reported a failed patellar component in total knee arthroplasty, with elevated serum titanium at least 20 times higher than normal values [16,21]. The highest titanium serum concentrations of our series were found in cases of mechanical complications such as stem fixation (subsidences) or neck impingement.…”
Section: Discussionmentioning
confidence: 48%
“…In our study, medians were constant in range up to a mean follow-up of nine years in both unilateral and bilateral hip replacement groups and were always under the DL. The low serum concentrations observed are reassuring with regard to some concerns about potential titanium toxicity [16]. Although titanium is considered safe except for its potential osteolytic activity, it circulates throughout the body and particles have been found in hair, lungs, brain, urine and serum [16].…”
Section: Discussionmentioning
confidence: 96%
“…Studies of metal ion levels in patients with spinal implants are less numerous. There have been only a few retrospective reports of metal ion levels in patients with stainless steel [18][19][20][21][22] and titanium [23,24] posterior spinal instrumentation. Less is known for metalon-metal total disc arthroplasty [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…For hand applications the irritation of overlying free gliding tendons in contact with the plate is also of concern (Nazzal et al, 2006). Furthermore, the negative influence of metal ions and salts on adjacent tissues and organs is well documented (Case et al, 1994: Kasai et al, 2003: Keegan et al, 2007Summer et al, 2007). Device extraction in children can further cloud the matter (Rosson and Shearer, 1991;Kahle, 1994;Alzahrani et al, 2003;Kim et al, 2005;Peterson, 2005;Busam et al, 2006).…”
Section: Introductionmentioning
confidence: 99%